Inferior oncological prognosis of surgery without oral chemotherapy for stage III colon cancer in clinical settings - Tashiro, Jo (BioMed Central, 2014)
BACKGROUND: Cancer patients not admissible for adjuvant chemotherapy are generally at high risk of considerably inferior prognosis. The aim of this retrospective study was to evaluate poorer survival without administration of oral adjuvant chemotherapy of stage III colon cancer patients in clinical settings. METHODS: Between April 2007 and September 2011, 259 patients with stage III colon cancer who underwent curative surgery were retrospectively assigned to the adjuvant chemotherapy group of 171 patients (66%) and the surgery alone group of 88 patients. Oral fluorouracil (5-FU) derivatives used in adjuvant chemotherapy, such as oral uracil and tegafur plus leucovorin (UFT/LV) or capecitabine, were the most commonly used. RESULTS: The 3-year relapse-free survival (RFS) rates were 74.9% for all cases, 58.3% for the surgery alone group, and 83.4% for the adjuvant chemotherapy group (P = 0.0001). The chemotherapy group was associated with a dramatic improvement in survival for stage IIIB (surgery alone 57.7% versus adjuvant chemotherapy 83.9%; P = 0.0001) and stage IIIC (surgery alone 18.2% versus adjuvant chemotherapy 57.3%; P = 0.006) patients. There was a significant difference in the overall recurrence rate between groups (surgery alone 35.2% versus adjuvant chemotherapy 18.1%; P = 0.002). Multivariate analysis identified adjuvant therapy as an independent predictive factor of reduced recurrence (hazard ratio (HR): 3.231; P = 0.004) and improved RFS (HR: 2.653; P = 0.001). CONCLUSION: In clinical settings, adjuvant therapy was the only significant prognostic factor of survival. Since many patients prefer not to receive chemotherapy, it is critical to inform stage III colon cancer patients that chemotherapy raises their chances of survival by three-fold compared with curative surgery alone.